Pengaruh Perputaran Total Aset, Likuiditas, Modal kerja, dan Solvabilitas Terhadap Profitabilitas pada Perusahaan Manufaktur yang Terdapat di Bursa Efek Indonesia Periode 2016-2020 - Selly Angel Josephine Selly; Mahmuddin Syah Lubis, S.E., M.Si. (Fakultas Ekonomi Prodi Akuntansi, 2022)
This research aims to analyze the effect of Total Asset Turnover, Liquidity, Working Capital, and Solvency on Profitability in Manufacturing Companies listed on the Indonesia Stock Exchange in the 2016-2020 period. The method that researcher used in this study is associative quantitative method. The population of this study were 193 manufacturing companies and a sample of 79 data was obtained through purposive sampling with data consisting of 5 years. The results showed that Total Asset Turnover, Liquidity, and Working Capital have significant effect on Profitability in Manufacturing Companies listed on the Indonesia Stock Exchange in 2016-2020. While Solvency has no effect on Profitability in Manufacturing Companies listed on the Indonesia Stock Exchange in 2016-2020. Keywords : Total Asset Turnover, Liquidity, Working Capital, Solvency, Profitability